Ranitidine‐induced black tongue: A case report. Issue 6 (2nd October 2017) - Akcaboy, Meltem; Sahin, Sanliay; Zorlu, Pelin; Şenel, Saliha
Abstract: Black tongue is a rare, benign, self‐limiting disorder caused by certain conditions and some medications. We report the first case of a child diagnosed with black tongue associated with ranitidine use. We report our case to emphasize the rare side effect of this frequently used drug. Health care professionals should be aware of the likelihood of ranitidine‐induced black tongue in clinical practice.